From Petri net models to C implementation of digital controllers - Gomes, L. (2013)
This work presents a tool for automatic generation of controllers' implementation code from Petri nets models amenable to be deployed into common platforms using widely used high level programming languages, such as C, C++, and Java. The generated code is linked with platform specific functions, supporting different types of implementation platforms, ranging from low-cost microcontrollers to workstations, and including microcontroller IPs (Intellectual Property) to be embedded into FPGAs (Field Programmable Gate Arrays). The system controller behavior is modeled using IOPT (Input-Output Place-Transition) Petri Nets models, which are represented through PNML (Petri nets Mark-up Language) notation. A tool for automatic code generation was developed, which achieved this goal in cooperation with other developed tools within a model-based development framework. Application to an automation system composed by a set of distributed controllers is presented.